The Role of Fintech Lending in Supporting MSME Growth - Soukotta, Agnes (Yayasan Pendidikan Belajar Berdikari, 2024)
This study aims to explore the role of Fintech Lending in supporting the growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The results of the analysis show that the regression model used has strong statistical significance, with a significant F value (Sig. = 0.000). Of the three independent variables tested, only Frequency of Use of Fintech services is shown to have a significant influence on MSME Growth (Sig. = 0.003). The variables of Access to Fintech and Number of Landing did not show a significant effect. The Adjusted R Square value of 0.307 indicates that this model is able to explain 30.7% of the variability in MSME growth, which suggests there are other variables outside the model that also affect MSME growth.The findings highlight the importance of frequency of use of Fintech services in driving MSME growth and suggest that Fintech service providers strengthen their strategies to increase adoption and repeated use of services by MSMEs. This study also recommends further research to identify other factors that influence MSME growth in the context of Fintech Lending.